1981
DOI: 10.1192/bjp.139.6.506
|View full text |Cite
|
Sign up to set email alerts
|

First Admissions of Native-Born and Immigrants to Psychiatric Hospitals in South-East England 1976

Abstract: SummaryIn the past, birthplace has frequently been omitted in completing the Sheet, but in 1976, over 91 per cent of all first admissions to psychiatric hospitals in South-East England were analysed by birthplace, sex, age-group and marital status. First admissions for schizophrenia were five times the expected number for immigrants from New Commonwealth America (the West Indies), four times the expected number for immigrants from New Commonwealth Africa (mostly ethnic Asians) and three times the expected numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(52 citation statements)
references
References 9 publications
2
48
0
2
Order By: Relevance
“…migrants in the UK. I>5>6 Yet differences among migrant subgroups were still found: in a study of all first admissions in South England in 1976, Dean et al 7 found a five-fold increase in the rate of schizophrenia among 'Afro-Caribbeans', a four-fold increase among Africans, a three-fold increase among migrants from India, yet migrants from Pakistan and other Asian countries showed no increase in the rate of schizophrenia. Studies in other countries have also found an increased rate of schizophrenia among migrants with major differences within migrant subgroups.…”
Section: Introductionmentioning
confidence: 93%
“…migrants in the UK. I>5>6 Yet differences among migrant subgroups were still found: in a study of all first admissions in South England in 1976, Dean et al 7 found a five-fold increase in the rate of schizophrenia among 'Afro-Caribbeans', a four-fold increase among Africans, a three-fold increase among migrants from India, yet migrants from Pakistan and other Asian countries showed no increase in the rate of schizophrenia. Studies in other countries have also found an increased rate of schizophrenia among migrants with major differences within migrant subgroups.…”
Section: Introductionmentioning
confidence: 93%
“…These authors, presumably because their sample numbers were too small, did not consider the sexes separately and while they remarked on the, difference, they did not discuss it. Dean et al (1981), in a study of admissions of immigrants to mental hospitals in the four Thames regions in 1976, quoted age and sex specific figures for numbers of observed and expected first admissions, though only for patients given a diagnosis of schizophrenia and in very broad age bands. They commented on the consistency of the size of the excess across all of the eight age and sex groups they studied.…”
mentioning
confidence: 97%
“…Carpenter & Brockington (1980) found from hospital case notes in Manchester that rates of schizophrenia among West Indians were five times higher than those among Whites. Dean et al (1981), in south London, reported that rates of schizophrenia were five times higher in African-Caribbeans compared with their White counterparts (see Table 2). Littlewood & Lipsedge (1981) interviewed 36 patients who had presented to the hospital with symptoms of a religious fervour.…”
Section: Uk Studiesmentioning
confidence: 99%